2015
DOI: 10.1039/c5sm01406a
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial equation of state for ionized surfactants at oil/water interfaces

Abstract: A new mathematical approach has been developed for describing the interfacial behaviour of oil/water interfaces in the presence of ionic surfactants. The approach relies on the ideal behaviour of ionized surfactants at oil/water interfaces, which is previously demonstrated by Lucassen-Reynders (J. Phys. Chem., 1966, 70, 1777-1785). The new derived equation simply relates the interfacial tension to the surfactant molecular size and the cmc value of the surfactant in the aqueous phase. The predicted values are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…While the textbooks and review articles also show the surfactants and co-surfactants forming a monolayer at the surfaces of the oil droplets in a cream, we show here that this interfacial layer is very diffuse, suggesting that it is significantly roughened, with the constituent molecules not aligned but staggered. Again, this is entirely consistent with the observations made by Zarbakhsh et al 22,39,40,42,43 wherein the surfactant and lipid layers that form at oil-water interfaces are shown to exhibit a pronounced roughening which cannot be explained simply by thermal broadening and is considered to arise instead because of a staggering of the molecules' hydrocarbon chains brought about by their dissolution within the oil and the resultant disruption of their side-by-side packing.…”
Section: Discussionsupporting
confidence: 90%
“…While the textbooks and review articles also show the surfactants and co-surfactants forming a monolayer at the surfaces of the oil droplets in a cream, we show here that this interfacial layer is very diffuse, suggesting that it is significantly roughened, with the constituent molecules not aligned but staggered. Again, this is entirely consistent with the observations made by Zarbakhsh et al 22,39,40,42,43 wherein the surfactant and lipid layers that form at oil-water interfaces are shown to exhibit a pronounced roughening which cannot be explained simply by thermal broadening and is considered to arise instead because of a staggering of the molecules' hydrocarbon chains brought about by their dissolution within the oil and the resultant disruption of their side-by-side packing.…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Fig. 5b , SDS solution has lower IFTs in the salt solutions, as it is the characteristic of ionic surfactant systems 35 37 . The impact of nanoparticles on the interfacial tension of the surfactant solution weakens in the presence of NaCl and it completely vanishes at high concentrations.…”
Section: Resultsmentioning
confidence: 81%
“…6a and b ). The addition of electrolyte promotes the surfactant activity coefficient and accordingly increases its surface activity 35 , 38 (Fig. 6c ).…”
Section: Resultsmentioning
confidence: 97%
“…Several researchers analyzed adsorption to liquid–liquid interfaces by relating the profile of the IFT curve and the equilibrium tension to relaxation phenomena and surface excess concentration or coverage of adsorbents. The great number of adsorption isotherms and equations of state for surfactants alone demonstrate the divergent behavior of IFT to adsorption. For nanoparticles without surfactants, Du et al showed that the adsorption energies of individual particles to the oil–water interface can be treated as additive to the overall interfacial energy of the bare interface by assuming that no interactions occur between interfacially adsorbed particles until a close-packed layer is formed (as indicated by no further decrease in IFT upon increasing particle concentration). The consistency of this approach was validated using optical microscopy for microparticles.…”
Section: Introductionmentioning
confidence: 99%